Erbium anchored iminodiacetic acid (IDA) functionalized CoFe2O4 nano particles: an efficient magnetically isolable nanocomposite for the facile synthesis of 1, 8-naphthyridines. (19th June 2020) - Tamoradi, Taiebeh; Daraie, Mansoureh; Heravi, Majid M.; Karmakar, Bikash
Abstract : We report a novel magnetic catalyst for the synthesis of biologically important compounds. Abstract : A novel functional material was developed by immobilizing an Iminodiacetic acid–erbium (Er) complex onto the surface of magnetic spinel CoFe2 O4 nanoparticles. The obtained nanocomposite was fully characterized using different analytical techniques such as FT-IR, XRD, SEM, BET, EDX and X-ray atomic mapping analysis. The catalytic activity of this novel material was investigated in the successful synthesis of 1, 8-naphthyridine derivatives via a three component reaction involving 2-aminopyridine, malononitrile and various aryl aldehydes. The reactions ended up with excellent yields in short reaction times. The catalyst was reused seven times in the proposed reaction without appreciable loss of activity.